Patentability and de-extinct animals in Europe: the patented woolly mammoth?. Issue 1 (16th July 2020) - McMahon, Aisling; Doyle, David M
Abstract: De-extinction is a hot topic within conservation science but the potential patentability of de-extinct animals in Europe has hitherto been unexplored. This article addresses this lacuna, examining the legal, commercial, and ethical implications of patenting de-extinct animals under European patent law. The article is organized into four parts. Part I explores the reasons why patents are relevant and may be applied for in this context. Part II provides an overview of the scientific techniques currently being used in de-extinction projects, setting the foundation for the analysis of patentability which follows. Part III then critically assesses whether recreated animals would qualify as patent eligible subject matter under European patent law. It also investigates the extent to which European patent exclusions such as those on animal varieties, essentially biological processes, and the morality provisions might apply and whether recreated animals would meet the novelty requirement for patentability. Part IV concludes by highlighting the possible ramifications of patenting such animals, elucidating the chasm between the cultural and symbolic significance held by such animals, and their lack of differential treatment in the patent law sphere. It argues that de-extinction reignites questions around the scope of patents, and the role of ethical considerations within patent decision-making which warrant urgent reconsideration.